Experimental relationships between operating speeds of successive road design elements in two-lane rural highways - Eboli, Laura; Guido, Giuseppe; Mazzulla, Gabriella; Pungillo, Giuseppe (Transport, 2017)
Speed has been identified for a long time as a key risk factor in road traffic. Inappropriate speeds contribute to a relevant part of road crashes, and then to the mortality and disabilities resulting from them. Starting from this consideration this paper investigates road safety by analysing operating speed, which is the 85th percentile speed. Particularly, two regression models are proposed to predict operating speeds for different road elements related to specific road conditions. The case study is represented by a two-lane rural highway. Smartphone-equipped vehicles were used to evaluate the operating speed for each element of the analysed road segment. Continuous speed data were recorded by the vehicles driven by users with different driving behaviours. Since the lack of safety is often linked to an inconsistency roadway geometric design, we effected a preliminary quantitative design consistency evaluation that confirmed the need of having accurate experimental measures of operating speed or appropriate models for predicting it. We propose two types of operating speed models: one for estimating speed profiles for horizontal curves, and the other one for tangents. According to both models, operating speed is predicted by the combination of an independent variable representing a geometric characteristic (curve radius for the curves and length for the tangent elements) and an independent variable relating to the speed, and specifically the operating speed of the previous road element. The models show a good predictive capability, and can be considered as a useful tool for operators and technicians for road management.First published online: 01 Nov 2015